Two life-threatening complications during chronic total occlusion management - Maritsa, Dimitra; Gavrielatos, Gerasimos; Dimopoulos, Antonios; Patsourakos, Nikolaos; Papakonstantinou, Nikolaos; Pisimisis, Evaggelos (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
A 50-year-old man, with one-month effort angina and a history of hypertension and dyslipidemia, was subjected to coronary angiography (CA), via the left radial approach, which revealed single-vessel chronic total occlusion (CTO) of the mid-right coronary artery (RCA) (Figures 1: Ia, b). The left ventricle ejection fraction (LVEF) was 50% with hypokinesia at the infero-lateral wall. Since the patient was recently symptomatic with a positive stress test and a relatively low J-CTO Score ≈ 2, an ad-hoc percutaneous coronary intervention (PCI) was decided, with the patient’s informed consent. In our cath lab, for the last three years, there has been a newly engaged CTO program including two operators with ≥ 20 CTO procedures per year and a total volume of 50 CTOs/year and both of them were involved in the present procedure.